Distinctive Community Patterns With Exceptional Diversity of Polychaetes Around a Tectonically Active Archipelago in the Tropical Indian Ocean - Gopal, Aiswarya; Abdul Jaleel, K. U.; Parameswaran, Usha V.; Sanjeevan, V. N.; Saramma, A. V.; Vijayan, Anilkumar; Saravanane, N.; Gupta, G. V. M.; Sudhakar, M. (Frontiers in Marine Science, 2020)
Marine soft-sediments sustain functionally important benthic assemblages that are critical for remineralization of organic matter and supply of nutrients to the water column. While these assemblages are well studied along continental margins, investigations from insular margin that surround oceanic islands are very limited. This paper examines the distribution and standing stock of macrozoobenthos at 50, 100, and 200 m depth contours surrounding the Andaman and Nicobar archipelago in the tropical Indian Ocean. The standing stock of macrozoobenthos decreased from the mesophotic reef areas (50 m depth) to the deeper strata (200 m), particularly in the case of the dominant groups, the polychaetes and crustaceans. Smaller-sized, interstitial polychaetes and crustaceans were abundant in the coarser sandy sediments at the shallower sites. The polychaetes were represented by 606 species (279 genera) in the study, of which >50% were rare species. Based on polychaete species composition, three regions were delineated in the study area - the Nicobar margin, the western margin of the Andaman (Bay of Bengal sector), and the eastern margin of the Andaman (Andaman Sea sector). The long, uninterrupted Andaman Island chain formed a geographic barrier separating the eastern and western margins, resulting in the regional distinctions in sediment nature and hydrographic characteristics, which in turn influenced species distribution. Corresponding differences were absent in the case of the Nicobar Islands, which are widely separated by transecting channels, permitting exchange of water between the Bay of Bengal and the Andaman Sea. Within the three regions, polychaete communities changed significantly in taxonomic and functional composition with increasing depth. The well oxygenated, coarse sandy sediments around mesophotic reefs (50 m) harboured predator-dominated assemblages. The 200 m sites, which were characterised by oxygen minimum conditions (<0.5 ml.l-1), particularly around the Andaman Island mass, were dominated by deposit feeders. This study provides the first comprehensive dataset on distribution and standing stock of macrozoobenthos, and community structure of polychaetes along the Andaman and Nicobar insular margin. It also revealed the highest number of polychaete species ever recorded in the northern Indian Ocean, indicating that the Andaman and Nicobar margin is a significant marine biodiversity hotspot.